Functionalization of Silk Fibroin Materials at Mesoscale. (7th October 2016) - Lin, Naibo; Cao, Liwei; Huang, Qiaoling; Wang, Changyong; Wang, Yan; Zhou, Jin; Liu, Xiang‐Yang
Abstract : Silk fibers spun by silkworms or spiders at ambient temperature display unique mechanical strength, excellent biocompatibility and optical transparency, which offer unconventional interfaces to soft and curved biological systems. In comparison with conventional materials, the performance of soft matter, i.e., animal silks, is mainly determined by the structure at the mesoscale. To further extend the applications, functionalization of silk materials becomes is required, and mesoscopic material assembly (MMA) was developed for this task. This feature article provides an overview on the principles and strategies concerning MMA, and some typical examples of functionalizing silk fibroin materials. The main strategies of MMA include in vivo and in vitro assemblies, and can be implemented by the three different paths: (1) molecular recognition, (2) surface functionalization of nanomaterials, or (3) foreign molecule mediation. The cases include the functionalization of silk fibroin materials by one/two‐photon fluorescent molecules, quantum dots (QDs) and gold clusters, etc. The applications of these functionalized materials in bio waveguide, white‐light‐emitting devices, bioimaging, were also highlighted. MMA provides a practical tool for the production of the functionalized biocompatible materials, which can be further applied to fabricate high‐performance bio integrated devices used in consumer electronics, and biomedical diagnosis, as well as human‐machine interfaces. Abstract : Functional silk materials can be fabricated in vitro and in vivo by material assembly on the mesoscopic scale based on the understanding and controlling of the hierarchical structure. The knowledge of the functionalization of silk by mesoscopic material assembly should be translated in such a way that it can facilitate functionalization and rational design of materials in a controllable manner.